INFLAMMATION RESOLUTION MEDIATORS IN ACUTE HEART FAILURE. (June 2018) - Reina-Couto, M.; Bessa, J.P.; Serrão, P.; Afonso, J.; Roncon-Albuquerque, R.; Paiva, J. Artur; Albino-Teixeira, A.; Sousa, T.
Abstract : Objective: Acute heart failure (AHF) remains a major health concern, with high mortality and re-hospitalization rates and treatment being still largely opinion-based. Resolvins (Rvs), derived from omega-3-fatty acids, actively contribute to the resolution of inflammation and tissue regeneration and recent experimental findings suggest that their administration improves cardiac function after myocardial infarction. However, they remain scarcely explored in clinical settings of AHF. Therefore, we aimed to evaluate serum RvD1 and RvE1, and to determine their correlation with biomarkers of cardiac injury/dysfunction, proinflammatory/redox status and endothelial dysfunction in AHF. Design and method: Patients with the diagnosis of AHF (n = 10) and cardiogenic shock (CS) (n = 9) were included and blood samples were collected at admission and at days 3 to 5. Blood donors were used as controls (n = 10). RvD1, RvE1, nitrotyrosine (redox dysfunction biomarker) and endocan (endothelial dysfunction biomarker) were measured with ELISA kits. C-reactive protein (CRP), B-type natriuretic peptide, high-sensitivity troponin I and leukocyte count were evaluated using automated analyzers. Results: RvD1 values on admission were significantly higher in AHF than in CS (AHF: 2.98 ± 0.42 ng/mL vs CS: 1.39 ± 0.24ng/mL, p = 0.024) although there were no significant differences compared to controls values (controls: 1.84 ± 0.34; p = ns vs AHF or CS). On the other hand, RvE1 concentration on admission was significantly increased in patients with AHF and with CS (controls: 0.076 ± 0.018; AHF: 0.19 ± 0.040 ng/mL; CS: 0.23 ± 3.8ng/mL; controls vs AHF, p = 0.048; controls vs CS, p = 0.007). Furthermore, there was a significant trend for a linear increase between controls, AHF and CS (p = 0.003). There were no significant changes between Rvs values on admission and on later time points. We only observed positive correlations between RvE1 and CRP (r = 0.342, p = 0.041), neutrophil-to-lymphocyte ratio (r = 0.472, p = 0.006), nitrotyrosine (r = 0.395, p = 0.007) and endocan (r = 0.346, p = 0.018). Conclusions: These Rvs have distinct profiles in AHF, with RvE1 increasing with the severity of the clinical/hemodynamical condition in CS patients and being significantly associated with inflammatory/redox status and endothelial dysfunction. In contrast, RvD1, whose administration has been shown to be cardioprotective in experimental myocardial infarction, appears to be exhausted or inactivated in worse clinical scenarios in the spectra of AHF.